Short Communication - Chronic Rinorrhea - Qurrat-ul-Ain, Tayyaba Gul Malik, Muhammad Khalil, (Pakistan Journal of Ophthalmology, 2016)
A 15 – year old boy, resident of Lahore, was referred by medical department to eye OPD, for evaluation of his right drooping lid and double vision. It was associated with running nose and severe temporal headache. Past history revealed head trauma with loss of consciousness for ten minutes, eleven years back. It was followed by running nose on bending down. He had several episodes of meningitis after that trauma which settled without squeal. On examination, he had pupil involving third nerve palsy and chemical analysis of nasal discharge revealed CSF rhinorrhoea. The patient was referred to neurosurgical department for management. Conclusion: Careful history, examination and investigations remain key to the sensible management of patients. Patients with recurrent meningitis should be evaluated for a CSF leak. Keywords: CSF rhinorrhoea, third nerve palsy, intra cranial hypotension, Traumatic CSF leak.